Typhoon Positioning Method Using Dual-Radar Zero Radial Velocity Lines and Preliminary Test - Hongya Liu (Tropical Cyclone Research and Review, 2017)
ABSTRACT: Timely and relatively accurate detection of the center position of a near-landfalling typhoon is essential for weather forecasts, warning, disaster preparedness and data assimilation. Due to the vortex like nature of the flow near the typhoon center, the Zero Radial Velocity Line (ZRVL) of a Doppler radar extends through the typhoon center and the radar site. This paper proposes a method to detect the typhoon center by intersecting the ZRVLs of a dual-Doppler radar system. Simulation with Rankine Vortex model shows the validity of this method. This paper also evaluated the method by locating the centers of Typhoon FUNG-WONG (No. 201416) which impacted the east coastal regions of China from the afternoon of 22 September to the morning of 23 September, 2014 BST (Beijing Standard Time). During this period, the centers of the coastal typhoon were precisely positioned by intersecting the ZRVLs of two Doppler radars. The positioning accuracy of this method is comparable to that from Automatic Weather Stations (AWS) wind data. This method is suitable for areas where AWS data are unavailable, supposing radars are apart 100 km with a maximum unambiguous distance of 148km, this technique can cover most regions effectively. Keywords: dual radar, zero radial velocity line, typhoon positioning, coastal typhoon